IMPLEMENTATION OF WORK TRAINING PROGRAM FOR CORRECTION INTELLECTED CITIZENS (CASE STUDY IN CLASS II A JEMBER PRISON) - Muhammad Mapparenta Rewanda Kahar; Umar Anwar (Universitas Muhammadiyah Jember, 2022)
The purpose of this study is to implementation design strategies that are relevant to the implementation of job training in Jember Class II A Prison using the SWOT analysis method. The SWOT analysis will go through 3 matrices, namely the first, the IFE (Internal Factor Evaluation) matrix which will draw out the strengths and weaknesses of the workshops while the second, the EFE (External Factor Evaluation) matrix which will describe the threat and opportunity factors of the workshop. workshop and the third, IE (Internal External) matrix which will show the current work shop position. From the calculation, the highest weight of the strength factor is 0.15, the highest weight of the weakness factor is 0.15, the highest weight of the opportunity factor is 0.19, and the highest weight of the threat factor is 0.19. The average value of the IFE matrix is -0.16 and the EFE matrix is -0.1. From these results, the Jember Prison Workshops are in the 4th quarter and the strategy that must be implemented is defensive.Keyword: Implementation; Training, Work, SWOT, IFE and EFE